The importance of global shocks for national policymakers - Rising challenges for central banks - Ansgar Belke; Andreas Rees (Verein für Socialpolitik, 2010)
We analyze the importance of global shocks for the global economy and national policy makers. More specifically, we investigate whether monetary policy has become less effective in the wake of financial globalization. We also examine whether there is increasing uncertainty for central banks due to globalization-driven changes in the national economic structure. A FAVAR framework is applied to derive structural shocks on a worldwide level and their impact on other global and also national variables. We estimate our macro model using quarterly data from Q1 1984 to Q4 2007 for the G7 countries plus the euro area. According to our results, global liquidity shocks are a driving force of the global economy and various national economies. However, some other shocks originating in house prices, GDP, technology and long-term interest rate shocks play a role at the global level as well. These results prove to be robust across different specifications. Structural break tests indicate that global liquidity shocks have recently become more important as a determinant for house prices. In general, global variables have become more powerful over time in driving national variables.
Keywords: E58; F42; C32; 330; Global shocks; international business cycle; international policy coordination and transmission; factor augmented vector autoregressive (FAVAR) models; common factors